PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP PEGAWAI PADA BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) - Faisal Yunas; M. Ali Yusuf; Ena Triana; Dheila Ziehandiny (Melati Institute, 2022)
The purpose of this study was to determine: (1) The effect of job satisfaction and work motivation together on employee performance at the National Population and Family Planning Agency (BKKBN), (2) The effect of job satisfaction on employee performance at the National Population and Family Planning Agency ( BKKBN), (3) The effect of work motivation on employee performance at the National Population and Family Planning Agency (BKKBN). This study uses a quantitative approach. The sampling technique used saturated samples totaling 38 people. The data collection technique used is a questionnaire, which has been tested for its validity and reliability. The data analysis technique used is the Correlation Coefficient, Coefficient of Determination, Multiple Linear Regression, F-Test and T-Test using the SPSS version 24 program. The results show that job satisfaction (X1) and work motivation (X2) have a strong relationship to employee performance. (Y). This is evidenced by the calculation of the correlation coefficient of 0.643 and the calculation of multiple linear regression, namely Y = 1.571 + 0.558 X1 + 0.645 X2 + 0.766. In testing the F test hypothesis, the Fcount value is (12.337) > Ftable (3.26), meaning that there is a simultaneous positive and significant effect of job satisfaction and work motivation on employee performance. In testing the hypothesis T-test the job satisfaction variable (X1), the tcount value of (3.314)> ttable (2.028) means that job satisfaction partially has a positive and significant effect on employee performance. While the T-test on the work motivation variable (X2) obtained a tcount of (3.524) > ttable (2.028), meaning that work motivation partially has a positive and significant effect on employee performance. It can be concluded that the results of job satisfaction (X1) and work motivation (X2) affect employee performance (Y) at the National Population and Family Planning Agency (BKKBN) either simultaneously or partially.